Analysis of variance for functional data - Zhang, Jin-Ting (Chapman & Hall/CRC monographs on statistics and applied probability, 2014)
"Preface Functional data analysis has been a popular statistical research topic for the last three decades. Functional data are often obtained via observing a number of subjects over time, space or other continua densely. They are frequently collected from various research areas, including audiology, biology, children's growth studies, ergonomics, environmentology, me- teorology, and women's health studies among others in the form of curves, surfaces, or other complex objects. Statistical inference for functional data generally refers to estimation and hypothesis testing about functional data. There are at least two monographs available in the literature which are devoted in estimation and classi